2002
DOI: 10.1034/j.1600-0528.2002.300308.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral self‐care among adults with diabetes in Finland

Abstract: A need exists for further promotion of oral self-care among adults with diabetes. Support by dental and other health care professionals involved in diabetes care should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 32 publications
3
36
3
Order By: Relevance
“…The proportion of those who brushed more than twice daily (11.4%) was considerably lower than proportions reported by Karikoski (5,28). In a study of Finnish adults with diabetes, twice-daily brushing was reported by 50% of participants (12).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…The proportion of those who brushed more than twice daily (11.4%) was considerably lower than proportions reported by Karikoski (5,28). In a study of Finnish adults with diabetes, twice-daily brushing was reported by 50% of participants (12).…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies indicate that oral health may not be a priority for diabetic patients and that these patients are less likely than nondiabetic patients to have visited a dentist (23). Furthermore, it was reported that twice-daily toothbrushing is less common in diabetic patients than in nondiabetic patients (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regular oral health education performed by dental hygienists significantly improved plaque index, dental calculus index and community periodontal index (CPI) compared to simple education with printed materials for studies of individuals with diabetes and periodontal disease 13,14. Stringent oral hygiene combined with periodontal surgery substantially reduced periodontal pocket depth 15,16.…”
Section: Introductionmentioning
confidence: 99%